Enterotoxin production and serogroups of Campylobacter jejuni and Campylobacter coli from patients with diarrhea and from healthy laying hens. - Lindblom, G B (1989)
Enterotoxin production, a possible virulence factor, was determined in Campylobacter jejuni and Campylobacter coli by two different techniques, the CHO cell test and the GM1 enzyme-linked immunosorbent assay. The frequency of enterotoxigenic Campylobacter strains was 32% in strains from both humans with acute enteritis and healthy laying hens, as measured by the CHO cell test. The CHO cell test was significantly more sensitive than the GM1 enzyme-linked immunosorbent assay in the detection of enterotoxigenic strains. Enterotoxin production was compared with the presence of heat-stable and heat-labile antigens. There was no significant correlation between enterotoxin production and serogroups for C. jejuni or C. coli. The difference in enterotoxigenicity between C. jejuni (34.1%) and C. coli (21.9%) was not significant.